Intervención temprana de la lectura y la escritura en estudiantes españoles. - González-Valenzuela, María José; Martín-Ruiz, Isaías (Universidad de Murcia, 2023)
The aim of this paper is to analyse the reading and writing achievement of Spanish school children following an intervention con-ducted at an early age. The purpose of the intervention is to prioritise and systematise instruction in the alphabetic principles, phonological aware-ness, reading fluency, vocabulary, and text comprehension. The sample consists of 126 subjects, distributed between an instructed group (n=62) and an uninstructed group (n=64). All the subjects were from average so-cio-cultural areas, with normal intelligence and with no physical, mental, and/or sensory deficits. Subjects were evaluated from the second year of Early Years Education (4 years of age) up to the first year of Primary Edu-cation (six years of age). The design was longitudinal with repeated meas-urements (four assessments), three intervention phases, two study variables (reading achievement and writing achievement), and two groups of sub-jects. Descriptive statistical analysis and repeated measures analyses of var-iance were performed. The results obtained indicate higher scores in read-ing and writing throughout all the assessments and significantly greater progress in the instructed group. These results demonstrate the effective-ness of early intervention in written language through systematic instruc-tion in phonological awareness, the alphabetic principles, reading fluency, vocabulary, and text comprehension.
Effects of early reading and writing intervention on Spanish school children.
Keywords: Lectura - Aprendizaje; Escritura - Aprendizaje; Enseñanza - Innovaciones; Early intervention; Longitudinal study; Reading; Writing